2021
DOI: 10.3389/fmed.2021.709884
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hepatic Encephalopathy on Clinical Characteristics and Adverse Outcomes in Prospective and Multicenter Cohorts of Patients With Acute-on-Chronic Liver Diseases

Abstract: Importance: Hepatic encephalopathy is a severe complication, and its contribution to clinical adverse outcomes in patients with acute-on-chronic liver diseases from the East is unclear.Objective: We aimed to investigate the impact of hepatic encephalopathy on clinical characteristics and adverse outcomes in prospective and multicenter cohorts of patients with acute-on-chronic liver diseases.Design: We conducted a cohort study of two multicenter prospective cohorts.Setting: China.Participants: Acute-on-chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The incidence and prevalence of overt HE is higher in patients with alcohol-related cirrhosis than cirrhosis from other causes. 3,47 In a large study of Medicare patients, alcohol-related cirrhosis was most associated with incident HE. 3 The relationship between alcohol-related cirrhosis and CHE is less clear.…”
Section: Alcohol-related Liver Diseasementioning
confidence: 99%
“…The incidence and prevalence of overt HE is higher in patients with alcohol-related cirrhosis than cirrhosis from other causes. 3,47 In a large study of Medicare patients, alcohol-related cirrhosis was most associated with incident HE. 3 The relationship between alcohol-related cirrhosis and CHE is less clear.…”
Section: Alcohol-related Liver Diseasementioning
confidence: 99%
“…The North American Liver Failure Alliance (NACSELD) identified HE grades 3-4 as an independent predictor of 30-day mortality in hospitalized patients with cirrhosis, with 30-day mortality for HE grades 3-4 as high as 38% (32,33). Our previous study also demonstrated that the 28-day LT-free mortality rates were 34.5 and 55% for HE grades 3 and 4, respectively, among patients with cirrhosis and other chronic liver diseases (34). The results from the above studies and the results from our study demonstrated that grade 3-4 HE plays a more important role than the INR in the shortterm outcomes of patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 80%
“…The CLD, ALI, AD and AoCLD, as well as the exclusion criteria, have already been defined in published CATCH-LIFE manuscripts [ 3 , 13–15 ]. Acute-on-chronic liver failure (ACLF) [ 16 ] was defined according to the updated consensus recommendations of the European Association for the Study of Chronic Liver Failure consortium [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Chronic liver disease (CLD) is a growing cause of morbidity and mortality worldwide [ 1 ], particularly in low-to-middle income countries with a high economic burden and limited treatment availability [ 2 ]. Patients with CLD and acute events are considered to have acute-on-chronic liver disease (AoCLD) [ 3 ]. Acute events, including acute decompensation ( ad ) and acute liver injury (ALI), can aggravate liver dysfunction in patients with CLD and lead to liver failure if continued [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%